1998
DOI: 10.1177/0148607198022003127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin‐Like Growth Factor 1 on Neutrophil and Monocyte Functions in Normal and Septic States

Abstract: IGF-1 serves as a priming agent for biologic functions of leukocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
1
16
1
Order By: Relevance
“…From these findings, it was suggested that IGF-I expression in AMC may be linked to the state of cell activation. IGF-I has been shown to enhance phagocytic activity of neutrophils in vitro when they were challenged with E coli [54] . It was demonstrated by Inoue et al [55] that IGF-I increased the killing capacity and phagocytosis of peritoneal macrophages when they were activated by E coli.…”
Section: Nature Of Amcmentioning
confidence: 99%
“…From these findings, it was suggested that IGF-I expression in AMC may be linked to the state of cell activation. IGF-I has been shown to enhance phagocytic activity of neutrophils in vitro when they were challenged with E coli [54] . It was demonstrated by Inoue et al [55] that IGF-I increased the killing capacity and phagocytosis of peritoneal macrophages when they were activated by E coli.…”
Section: Nature Of Amcmentioning
confidence: 99%
“…Table 2 WBC and circulating leukocyte subpopulations determined by FACScan analysis of blood drawn from sham-operated mice (LAP), saline-treated septic mice (CLP), and septic mice treated with either GH (CLP/GH), IGF-I (CLP/IGF), or a combination of GH and IGF-I (CLP/G + I) In contrast to GH we observed an immunomodulatory effect of IGF-I. As for GH, an immunomodulatory effect of this peptide was proposed but data about an IGF-I-induced immunomodulation during systemic inflammation are limited [8,9,12,17,[26][27][28]41,42]. In general it was noticed that IGF-I promoted the proliferation and differentiation of myeloid lineage cells and lymphocyte precursor cells, augmented PMN bactericidal capacity and migration, and enhanced in vitro cytokine production [12,15,[26][27][28]41,42].…”
Section: Discussionmentioning
confidence: 83%
“…Dosages of GH ranging between 0.05 and 5 mg/ kg/day have been used and were effective in inducing a physiological response in humans and experimental animals [13,[18][19][20]. Concerning IGF-I these dosages range between 1 and 24 mg/kg/day [17,16,[21][22][23]. We therefore decided to use a moderate dosage of GH and IGF-I respectively that ensures a physiologic response.…”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, weaning is associated with an increase in somatotropin concentration and a decrease in the concentration of insulin-like growth factors 1 and 2 (IGF-1 and IGF-II) (Matteri et al 2000, Kojima et al 2008). Higher IGF-1 concentrations are correlated with greater microbicidal capacity (Balteskard et al 1998). Thus, the increase of corticosteroid serum levels (Liu et al 1999) is related to an inhibition of apoptosis and a more efϐicient elimination of apoptotic PMNLs by macrophages.…”
Section: Discussionmentioning
confidence: 99%